Исследование условий применения методики эластичной сети при проектировании телекоммуникационных систем - Агеев, Дмитрий Владимирович (Eastern-European Journal of Enterprise Technologies, 2009)
The modified elastic net method for solving the problem of backbone ring topology synthesis is offered. This method allows to find the shortest path for network backbone which take into consider internodes data traffic. The modified elastic net method usage condition for solving given problem study in this article experimentally.